The effect of autophagy-enhancing peptide in moisturizer on atopic dermatitis: a randomized controlled trial. (18th August 2019) - Kwon, Soon Hyo; Lim, Chae Jin; Jung, Juyeon; Kim, Heung Jae; Park, Keedon; Shin, Jung Won; Huh, Chang Hun; Park, Kyoung Chan; Na, Jung Im
Abstract: Background: Pentasodium tetracarboxymethyl palmitoyl dipeptide-12 (PTPD-12), a newly-synthesized peptide, enhances the autophagy activity, ultimately managing inflammation. Objective: To determine the effect of a new moisturizer containing PTPD-12 as the treatment of mild-to-moderate atopic dermatitis (AD). Methods: In this double-blind, randomized, placebo-controlled trial, 43 patients with mild-to-moderate AD were randomly assigned to either the PTPD-12 or control groups. Evaluations were performed at baseline, week 2, and week 4, including SCORing Atopic Dermatitis (SCORAD) index score, corneometry, trans-epidermal water loss (TEWL), visual analog scale (VAS) for pruritus, 7-point investigator's global assessment (IGA), and collection of adverse events. Results: The PTPD-12 group showed significant improvement with respect to SCORAD score, skin hydration, TEWL, and pruritus at weeks 2 and 4 when compared with baseline. Although the control group showed significant improvement regarding the SCORAD score and skin hydration, no significant change in TEWL or pruritus was demonstrated throughout the study. The mean changes in the SCORAD index score, skin hydration, TEWL, pruritus, and number of patients with improvement in IGA were not statistically different between the two groups. Conclusion: The moisturizer with autophagy-stimulating property provides a good therapeutic option to mild-to-moderate atopic dermatitis by contributing to skin barrier restoration and control of inflammation.